2006
DOI: 10.1093/nar/gnj013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic manipulation of an exogenous non-immunoglobulin protein by gene conversion machinery in a chicken B cell line

Abstract: During culture, a chicken B cell line DT40 spontaneously mutates immunoglobulin (Ig) genes by gene conversion, which involves activation-induced cytidine deaminase (AID)-dependent homologous recombination of the variable (V) region gene with upstream pseudo-V genes. To explore whether this mutation mechanism can target exogenous non-Ig genes, we generated DT40 lines that bears a gene conversion substrate comprising the green fluorescent protein (GFP) gene as a donor and the blue fluorescent protein (BFP) gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…The frequency of mutation events was calculated by dividing all mutation events by the total analyzed nucleotide numbers. An artificial GCV substrate, G/B construct was also used to analyze hypermutation frequency in DT40-SW cells as described previously (39). AID expression in DT40-SW cells were switched on, and single cells expressing AID (AID-ON cells) were sorted as described previously (40).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of mutation events was calculated by dividing all mutation events by the total analyzed nucleotide numbers. An artificial GCV substrate, G/B construct was also used to analyze hypermutation frequency in DT40-SW cells as described previously (39). AID expression in DT40-SW cells were switched on, and single cells expressing AID (AID-ON cells) were sorted as described previously (40).…”
Section: Methodsmentioning
confidence: 99%
“…4C). In addition, reporterbased assays for GCV using the G/B construct showed that overexpression of SRSF1-3 in wild-type DT40 cells did not induce GCV in the reporter construct placed in the ovalbumin locus, in which the AID-dependent hypermutation machinery has been shown to be inactive (39) (Fig. 3E).…”
Section: Srsf1-3 Has a Critical Role In Targeted Induction Of Hypermumentioning
confidence: 99%
“…The on-going Ig gene conversion and hypermutation in RAD51 paralogue mutants have likewise been employed to optimize the antigen specificity of antibodies (Cumbers et al 2002). Furthermore, a blue fluorescent protein gene together with a GFP pseudogene has been inserted into the IgL locus demonstrating that non-Ig transgenes can be diversified by gene conversion when inserted into the IgL locus together with a conversion donor sequence (Kanayama et al 2006).…”
Section: Application To Biotechnologymentioning
confidence: 99%
“…A recent report used a stop codon reversion assay to examine GCV of an artificial substrate containing a transcription cassette and an upstream homologous sequence donor in DT40 cells (27); results showed that the unit underwent GCV in the IgL locus but not in a non-Ig locus, suggesting that GCV is limited to Ig regions. There could be two explanations for the differences in the results of that study compared with those reported here.…”
Section: Generation and Integration Of Heterologous Transcriptionmentioning
confidence: 99%